2016
DOI: 10.1186/s12967-016-0765-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy outcome predictive effectiveness by the Oncogramme: pilot trial on stage-IV colorectal cancer

Abstract: BackgroundColorectal cancer (CRC) remains a major public concern. While conventional chemotherapeutic regimens have proved useful against advanced/metastatic diseases, progresses are to be made to effectively cure the large portion of patients not benefiting from these treatments. One direction to improve response rates is to develop chemosensitivity and resistance assays (CSRAs) efficiently assisting clinicians in treatment selection process, an already long preoccupation of oncologists and researchers. Sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…We identified 10 prognostic scores, [13][14][15][17][18][19][20][22][23][24] 3 nomograms, 16,21,25 and 1 chemotherapy sensitivity and resistance assay. 26 Of the 14 tools, Embase "colon tumor"/exp OR "colorectal tumor"/exp OR "colonic neoplasm*":ab,ti OR "colon neoplasm*":ab,ti OR "cancer of colon":ab,ti OR "cancer of the colon":ab,ti OR "colon cancer*":ab,ti OR "colonic cancer*":ab,ti OR "colorectal neoplasms*":ab,ti OR "colorectal tumor*":ab,ti OR "colorectal tumour*":ab,ti OR "colorectal carcinoma*":ab,ti OR "colorectal cancer*":ab,ti AND "decision support system"/exp OR "nomogram"/exp OR "probability"/exp OR "decision support system*":ab,ti OR "decision support technique*":ab,ti OR "decision aid*":ab,ti OR "decision support model*":ab,ti OR "decision analys*":ab,ti OR decision AND modeling:ab,ti OR "prediction rule*":ab,ti OR probabilit*:ab,ti OR nomogram*:ab,ti OR (prognos*:ab,ti AND (index:ab,ti OR score*:ab,ti OR model*:ab,ti)) OR markov:ab,ti AND "prognosis"/exp OR "incidence"/exp OR "mortality"/exp OR "follow up"/exp OR predict*:ab,ti OR course*:ab,ti OR mortalit*:ab,ti OR "life expectancy"/exp OR "survival rate"/exp OR "longevity"/exp OR "longevity":ab,ti OR "life expectancy":ab,ti OR "life expectance":ab,ti OR "life expectation":ab,ti OR "survival":ab,ti OR prognos*:ab,ti OR toxicit*:ab,ti OR "toxic potential*":ab,ti OR "margin of safety":ab,ti OR "adverse effect*":ab,ti AND ("article"/it OR "article in press"/it OR "review"/it) Cochrane Library "Incidence" OR mortality OR follow up studies OR prognos* OR predict* OR course* OR mortalit* OR "life expectancy" OR "longevity" OR "life expectancy" OR "life expectance" OR "life expectation" OR "survival" OR toxicit* OR toxic potential* OR "margin of safety" OR adverse effect* OR survival:ti,ab,kw AND "decision support system*" OR "decision support technique*" OR "decision aid*" OR "decision support model*" OR "decision analys*" OR "decision modeling OR prediction rule*" OR nomogram* OR (prognos* and (index or score* or model*)) or markov:ti,ab,kw AND "colonic neoplasm*" OR "colon neoplasm*" OR "cancer of colon" OR "cancer of the colon" OR "colon cancer*" OR "colonic cancer*" OR "colorectal neoplasms*" OR "colorectal tumor*" OR "colorectal tumour*" OR "colorectal carcinoma*" OR "colorectal cancer*":ti,ab,kw Cutoffs were determined by when the last major changes in treatment advice were introduced in the Dutch treatment guidelines (which roughly coincided with international guidelines).…”
Section: Dss Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 10 prognostic scores, [13][14][15][17][18][19][20][22][23][24] 3 nomograms, 16,21,25 and 1 chemotherapy sensitivity and resistance assay. 26 Of the 14 tools, Embase "colon tumor"/exp OR "colorectal tumor"/exp OR "colonic neoplasm*":ab,ti OR "colon neoplasm*":ab,ti OR "cancer of colon":ab,ti OR "cancer of the colon":ab,ti OR "colon cancer*":ab,ti OR "colonic cancer*":ab,ti OR "colorectal neoplasms*":ab,ti OR "colorectal tumor*":ab,ti OR "colorectal tumour*":ab,ti OR "colorectal carcinoma*":ab,ti OR "colorectal cancer*":ab,ti AND "decision support system"/exp OR "nomogram"/exp OR "probability"/exp OR "decision support system*":ab,ti OR "decision support technique*":ab,ti OR "decision aid*":ab,ti OR "decision support model*":ab,ti OR "decision analys*":ab,ti OR decision AND modeling:ab,ti OR "prediction rule*":ab,ti OR probabilit*:ab,ti OR nomogram*:ab,ti OR (prognos*:ab,ti AND (index:ab,ti OR score*:ab,ti OR model*:ab,ti)) OR markov:ab,ti AND "prognosis"/exp OR "incidence"/exp OR "mortality"/exp OR "follow up"/exp OR predict*:ab,ti OR course*:ab,ti OR mortalit*:ab,ti OR "life expectancy"/exp OR "survival rate"/exp OR "longevity"/exp OR "longevity":ab,ti OR "life expectancy":ab,ti OR "life expectance":ab,ti OR "life expectation":ab,ti OR "survival":ab,ti OR prognos*:ab,ti OR toxicit*:ab,ti OR "toxic potential*":ab,ti OR "margin of safety":ab,ti OR "adverse effect*":ab,ti AND ("article"/it OR "article in press"/it OR "review"/it) Cochrane Library "Incidence" OR mortality OR follow up studies OR prognos* OR predict* OR course* OR mortalit* OR "life expectancy" OR "longevity" OR "life expectancy" OR "life expectance" OR "life expectation" OR "survival" OR toxicit* OR toxic potential* OR "margin of safety" OR adverse effect* OR survival:ti,ab,kw AND "decision support system*" OR "decision support technique*" OR "decision aid*" OR "decision support model*" OR "decision analys*" OR "decision modeling OR prediction rule*" OR nomogram* OR (prognos* and (index or score* or model*)) or markov:ti,ab,kw AND "colonic neoplasm*" OR "colon neoplasm*" OR "cancer of colon" OR "cancer of the colon" OR "colon cancer*" OR "colonic cancer*" OR "colorectal neoplasms*" OR "colorectal tumor*" OR "colorectal tumour*" OR "colorectal carcinoma*" OR "colorectal cancer*":ti,ab,kw Cutoffs were determined by when the last major changes in treatment advice were introduced in the Dutch treatment guidelines (which roughly coincided with international guidelines).…”
Section: Dss Characteristicsmentioning
confidence: 99%
“…[17][18][19][20][21][22] Eight of the DSSs identified were developed and/ or only validated in Asian [13][14][15]25 or European populations. 16,20,21,26 Furthermore, great variation was found in the factors included in the DSSs. Only 3 factors were incorporated in > 2 DSSs (ie, patient age, performance status, and distant metastasis location; Figure 3).…”
Section: Ellen G Engelhardt Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Patient-derived models of cancer, including PDCOs show great promise in trialling therapies before they reach the patient and evidence supporting how accurately these ex vivo models can predict patient response is beginning to emerge [32,[38][39][40][41][42]. A recent report showed convincing data from ten patients that a viability assay could be used to predict patient response to irinotecan-based therapies using CRC-derived PDCOs [39].…”
Section: Discussionmentioning
confidence: 99%
“…Viable and dead cells are counted using a fluorescent microscope. Preliminary studies in metastasized colorectal cancer specimen reported a good sensitivity (84.6%) for the assay, although specificity was low at 33.3% .…”
Section: The Functional Approach: Chemoresponse Assaysmentioning
confidence: 98%